Isolated hard photon emission in hadronic Z° decays - Dova, María Teresa (1992)
We report on a study of energetic, isolated photons in a sample of ~ 320 000 Z ° hadronic decays. Energetic isolated photons probe the short-distance structure of QCD. We compare our data with the prediction of several QCD-based calculations. A search for new processes with one or two photons in the hadronic final state is also presented. No evidence for physics beyond the standard model is found.